Evaluating the Effectiveness of the SQ3R Learning Model on Students’ Islamic Religious Education Outcomes - Aprilian, Lucky Yoga; Baharudin, Baharudin; Azizah, Nurul; Zulaikhah, Siti; Yusnita, Erni (Journal of Innovation and Research in Primary Education, 2025)
This study aimed to examine the effectiveness of the SQ3R learning model on students’ cognitive learning outcomes in Islamic Religious Education (IRE) for seventh-grade students at SMP Negeri 1 Bandar Lampung. A quasi-experimental method with a posttest-only control group design was employed. The sample comprised two randomly selected classes: an experimental group (N = 32) taught using the SQ3R model and a control group (N = 32) taught using conventional methods. Data were collected through a validated and reliable multiple-choice posttest assessing cognitive domains of understanding (C2), analyzing (C4), and evaluating (C6). Data analysis included normality testing (Kolmogorov-Smirnov), homogeneity of variance (Levene’s test), independent samples t-test, and effect size calculation (Cohen’s d). Results revealed a statistically significant difference between groups (t(62) = 2.71, p = 0.009), with the experimental group achieving a higher mean score (M = 79.15, SD = 6.10) compared to the control group (M = 73.20, SD = 7.30). The effect size (Cohen’s d = 0.88) indicated a large effect. These findings confirm that the SQ3R model significantly enhances students’ cognitive learning outcomes, particularly in higher-order thinking skills. The study supports implementing the SQ3R learning strategy as a practical approach to improve academic performance in Islamic Religious Education.